Nedocromil sodium: a new drug for the management of bronchial asthma. - Lal, S (1984)
Nedocromil sodium (FPL 59002) is a pyranoquinoline dicarboxylic acid that has been developed for the management of bronchial asthma. We report the results of a double blind group comparative trial in which the disodium salt of nedocromil delivered by pressurised aerosol and a placebo were compared in the management of patients with a diagnosis of bronchial asthma who entered the double blind period on a minimum dose of beclomethasone dipropionate. In almost all the assessments of clinical activity nedocromil sodium was shown to be more effective than placebo. These include improvements in diary card symptom scores, reduction in concomitant use of a bronchodilator aerosol, and patients' and investigators' assessments of efficacy. Unwanted effects were few and mild. No patients were withdrawn from the trial.